Validitas dan Reliabilitas Soal USBN (Ujian Sekolah Berstandar Nasional) Tahun 2019 SMA Negeri Se- Kota Makassar - S. Salmiah Sari; Aisyah Aziz; Nurhayati Nurhayati (Seminar Nasional LP2M UNM, 2019)
This study aims to describe the distribution of substantial in accordance with outline structure of USBN questioning and to analyze the quality of the questions based on questions validity, the reliability coefficient, difficulty and diversity of multiple choice on USBN (Ujian Sekolah Berstandar Nasional) Batch 2018/2019 with Physic grade Senior High Schools. Kinds of this research is quantitative descriptive. Data of this study were collected by two methods, documentation and interview. Population of this research is Senior High School at Makassar City and samples were taken 4 schools. Technical analysis used Microsoft Excel and SPSS version 16. Outcome of this research showed the quantity of questions cover all topics and spreads in all class X topics with 31,43%, Class XI 37,14% and Class XII 31,42% and showed 1 point of the question is invalid, with the highest reliability coefficient is 0.91, the questions adversity at the easy level amount of 18 numbers (51,43%), mid-level amount of 16 numbers (45,71%) and hard level amount of 1 number (2,86%). Questions diversity on magnificent category amount of 12 numbers (34,28%), good category amount of 8 numbers (22,86%), adequate category amount of 7 numbers (20,00%), poor category amount of 8 numbers (22,86%).